Integration of Traditionalism of KH. Hasyim Asy'ari, KH. Ahmad Dahlan and Progresivism of John Dewey in Religious Moderation - Wahyudi Saputra Irawan; Ibnu Habibi; Prasetiya, Benny (Green Publisher, 2026)
This research aims to conceptually examine the integration of traditionalism in the thought of KH. Hasyim Asy'ari, Kh Ahmad Dahlan and progressivism according to John Dewey in the context of education, focusing on progressivism as the basis for religious moderation-based education. The study focuses on how both thoughts are understood as a foundation for human formation through the educational process, identifying common ground, differences, and possibilities for integration within the educational framework. This research uses a literature study method, examining the main works of KH Hasyim Asy'ari and John Dewey, as well as relevant scientific sources discussing religious moderation education, traditionalism, and progressivism. The results show that KH. Hasyim Asy'ari's thought, as an Indonesian traditionalist scholar, emphasizes the importance of morals, scientific sanad, and balance between religious knowledge and general knowledge. Meanwhile, John Dewey, an American progressive philosopher, emphasizes education as a process of experience, freedom of thought, and adaptation to social change. The synthesis between KH. Hasyim Asy'ari's traditional values and John Dewey's progressive ideas produces a moderate education concept that balances spiritual, intellectual, and social aspects. Religious moderation-based education inspired by these two figures can be an alternative model in facing the challenges of radicalism and moral degradation in the modern era.